2018
DOI: 10.1074/jbc.ra118.004952
|View full text |Cite
|
Sign up to set email alerts
|

Structural and kinetic analyses of penicillin-binding protein 4 (PBP4)-mediated antibiotic resistance in Staphylococcus aureus

Abstract: Edited by Chris Whitfield Methicillin-resistant Staphylococcus aureus (MRSA) causes serious community-acquired and nosocomial infections worldwide. MRSA strains are resistant to a variety of antibiotics, including the classic penicillin and cephalosporin classes of ␤-lactams, making them intractable to treatment. Although ␤-lactam resistance in MRSA has been ascribed to the acquisition and activity of penicillin-binding protein 2a (PBP2a, encoded by mecA), it has recently been observed that resistance can also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 56 publications
1
38
0
Order By: Relevance
“…It can be assumed that pbp4 expression is tightly controlled, as it is dynamically tuned in response to local antibiotic concentrations [49]. Recently, studies have shown that PBP4 may play an important role in S. aureus resistance to β-lactam antibiotics [40,[50][51][52][53]. Therefore, other factors contributing to the regulation of pbp4 activity should be investigated further, including wall teichoic acids, shown to act as spatial and temporal regulations of PBP4 mediated peptidoglycan crosslinking [54], and PBP2, which has been shown to interact with PBP4 during cell wall synthesis [55].…”
Section: Plos Pathogensmentioning
confidence: 99%
“…It can be assumed that pbp4 expression is tightly controlled, as it is dynamically tuned in response to local antibiotic concentrations [49]. Recently, studies have shown that PBP4 may play an important role in S. aureus resistance to β-lactam antibiotics [40,[50][51][52][53]. Therefore, other factors contributing to the regulation of pbp4 activity should be investigated further, including wall teichoic acids, shown to act as spatial and temporal regulations of PBP4 mediated peptidoglycan crosslinking [54], and PBP2, which has been shown to interact with PBP4 during cell wall synthesis [55].…”
Section: Plos Pathogensmentioning
confidence: 99%
“…Presumably in order to accommodate the added steric demand of this collaboration, a new, longer amino terminus for acyl‐enzyme acceptance is created by addition of a (Gly) 5 pentapeptide to the ε‐amine of the lysine . Moreover, yet additional crosslinking activity is provided by a second transpeptidase (PBP4) either as a result of resistance mutation and/or increased expression . Hence, S. aureus has two primary resistance mechanisms against β‐lactam antibiotics: the plasmid‐encoded BlaZ β‐lactamase (useful against early‐generation β‐lactams) and PBP2a (useful against all but the most recent generation of β‐lactams, such as ceftaroline and ceftobiprole).…”
Section: Sensing and Evading The β‐Lactam Antibiotics By A Gram‐positmentioning
confidence: 99%
“…[149][150][151][152] Moreover, yet additional crosslinking activity is provided by a second transpeptidase (PBP4) either as a result of resistance mutation and/or increased expression. [153][154][155][156][157][158] Hence, S. aureus has two primary resistance mechanisms against β-lactam antibiotics: the plasmid-encoded BlaZ β-lactamase (useful against early-generation β-lactams) and PBP2a (useful against all but the most recent generation of β-lactams, such as ceftaroline and ceftobiprole). As noted previously, both resistance mechanisms are activated only when S. aureus detects the presence of a β-lactam.…”
Section: Sensing and Evading The β-Lactam Antibiotics By A Gram-posmentioning
confidence: 99%
See 1 more Smart Citation
“…The hallmark of Methicillin resistant Staphylococcus aureus (MRSA) is the proliferation of antimicrobial resistance and MRSA nasal carriage often precedes infection [1]. The feat of this bacterium as a pathogen is directly linked to its range of virulence and immune evasion factors that enable the bacterium to dodge host defenses [2].…”
Section: Introductionmentioning
confidence: 99%